My experience with the office of Additional Solicitor General of India - "Bhattacharyya, Bishwajit" (New Delhi, 2013)
The Author shares his experience as Additional Solicitor General of India and takes a very positive view about India's future, pinning his hopes on India's youth. He writes contemporaneously, never written earlier by an incumbent of this office, on completion of 3 years tenure. The book should be of immense interest to every lawyer, judge, academician, government official, policy maker, and every person the world over interested in knowing the fist hand experience of a top law officer of the largest democracy in the world. A Unique book of its kind, it utility rises above time. In his book, Bishwajit talks candidly about his experiences and ordeals while holding the post of ASG and also exposes shocking details on how the Central Agency (that handles the government litigation) is managing its tax cases worth thousands of crores in the courts.
Keywords: Lawyers-India